Educação e catequese : o catecumenato como processo de iniciação à vida cristã na Diocese de Caxias do Sul/RS - Dalsotto, Mariana Parise Brandalise (My University, 2017)
This dissertation aims to think about the Catechetical practice in the Diocese of Caxias do Sul, performed on the guidance of two collections formulated for this practice, relating it to the Catechumenate (guided by the Catholic Church) and understanding it as an educational practice. In order to achieve this objective, documentary analysis, narrative interviews and focus groups were carried out. The documentary analysis was made by taking the documents written by Catholic Church that define and direct catechetical practice directly or indirectly, among them the Second Vatican Council, the General Directory for Catechesis, the Catechism of the Catholic Church, the Rite of Christian Initiation of Adults, The Document of Aparecida. The narrative interviews were carried out with the purpose of knowing how the two collections that are used in the mentioned diocese to the catechetical practice were constructed, being two interviews about each collection. This choice was also due to the recent temporal delimitation (year 2000), the beginning of the mobilization of the Diocese for the formulation of those new collections. The focus groups were mobilized to know the collections from the perspective of the catechists who use them, with a focal group for each collection and a session for each group. From this empirical corpus, it was possible to relate the cachectic practice with the educational practice. In order to define the latter and use its own concepts that could help the catechetical practice, the theoretical reference used was Paulo Freire´s thought (1983, 2004, 2005), once he tinks education as a process of human formation. The research was divided in five chapters, the first being the preliminar considerations that seek to present some definitions of the concepts of Catechesis, Catechumenate and Christian Initiation, as well as the theoretical and methodological choices made to develop this research. In the second chapter, it was presented the documentary analysis, through which it is possible to understand the orientations of the Catholic Church so that the Catechumenate may be taken as a model for catechesis. The third chapter seeks to present the collections used in the practice of catechesis in the Diocese of Caxias do Sul, and the fourth chapter intends to present the relation of catechesis, as a human formation, and its characteristics exposed in the two previous chapters with the Freirean thought about education. It was mobilized the concepts of conscientization, humanization, formation, social praxis, autonomy, dialogicity, among others. Thus, it is possible to conclude that catechesis is a form of education, of human formation, that can use educational thought to improve its practices and understand its role in the Catholic community. The role of education is precisely to help catechists understand that they are part of a formative process that assists in the constitution of the Christian being. This understanding, in turn, with the help of educational theories, can make this practice more meaningful for catechizers, making them builders of their own faith. This process of education for the faith never ends, as well as human formation, and catechesis is the period in which this formation will have its foundations for the search for the being more and the unprecedented-viable Christian being.
Esta dissertação tem como objetivo pensar a prática Catequética na Diocese de Caxias do Sul realizada a partir da orientação de duas coleções formuladas para esta prática, relacionando-a ao Catecumenato (orientado pela Igreja Católica) e entendendo-a como uma prática educacional. Para que este objetivo pudesse ser atendido, foram realizadas análise documental, entrevistas narrativas e grupos focais. A análise documental foi feita tomando os documentos escritos pela Igreja Católica que definem e orientam a prática catequética direta ou indiretamente, entre eles o Concílio Vaticano II, o Diretório Geral para a Catequese, o Catecismo da Igreja Católica, o Ritual da Iniciação Cristã de Adultos, o Documento de Aparecida. As entrevistas narrativas foram realizadas com o objetivo de conhecer como foram construídas as duas coleções que são utilizadas na referida diocese para a prática catequética, sendo duas entrevistas sobre cada coleção. Esta escolha se deu também em função da delimitação temporal recente (ano 2000), início da mobilização da Diocese para a formulação destas novas coleções. Os grupos focais foram mobilizados para conhecer as coleções a partir do olhar dos catequistas que as utilizam, sendo realizado um grupo focal para cada coleção, e uma sessão para cada. A partir deste corpus empírico, foi possível relacionar a prática caquética com a prática educacional. Para definir esta última e utilizar conceitos próprios dela que poderiam auxiliar a prática catequética, o referencial teórico utilizado foi o pensamento de Paulo Freire (1983; 2004; 2005), uma vez que este pensa a educação como um processo de formação humana. A pesquisa realizada foi dividida em cinco capítulos, sendo o primeiro as considerações iniciais que buscam apresentar algumas definições dos conceitos de Catequese, Catecumenato e Iniciação Cristã, bem como as escolhas teóricas e metodológicas realizadas para desenvolver esta pesquisa. No segundo capítulo, foi apresentada a análise documental, por meio da qual é possível entender as orientações da Igreja Católica para que o Catecumenato seja tomado como modelo para a catequese. O terceiro capítulo busca apresentar as coleções utilizadas na prática da catequese na Diocese de Caxias do Sul e o quarto busca apresentar a relação da catequese, enquanto formação humana e suas características expostas nos dois capítulos anteriores com o pensamento freireano acerca da educação. Foram mobilizados os conceitos de conscientização, humanização, formação, práxis social, autonomia, dialogicidade, entre outros. Assim, é possível concluir que a catequese é uma forma de educação, de formação humana, que pode se utilizar do pensamento educacional para aprimorar suas práticas e entender seu papel na comunidade católica. O papel da educação se coloca justamente no sentido de poder auxiliar que os catequistas entendam que fazem parte de um processo formativo que auxilia na constituição do ser cristão. Este entendimento, por sua vez, junto ao auxílio das teorias educacionais, pode tornar esta prática mais significativa para os catequizandos, tornando-os construtores de sua própria fé. Este processo de educação para a fé nunca se acaba, assim como a formação humana, sendo a catequese o período no qual esta formação terá suas bases para a busca pelo ser mais e pelo inédito-viável do ser cristão.
Keywords: Catequese - Estudo e ensino; Educação; Ensino religioso; Catechetics - Study and teaching; Education; Religious education